(untitled) (Bangladesh Agronomy Journal, 2017)
A field experiment was conducted at the research field of the Spices Research Centre, Shibganj, Bogra, Bangladesh in the summer season of 2013-2014 to find out the response of summer onion (var. BARI Peaj-3) to different levels and sources of potassium application. The experiment was laid out in a randomized complete block design with three replications. Potassium fertilizer combinations were comprised of four levels (0, 60, 120 and 180kg ha -1) and two potassium sources viz. Potassium Chloride (KCl) and Potassium Sulphate (K2SO4). A significant improvement in different growth and yield parameters of onion was observed in response to different sources and levels of potassium. The results indicated that the maximum plant height, leaves plant-1, length of leaf, length of bulb, diameter of bulb, average bulb weight, number of bulb per m2 and yield of bulbs were obtained from the onion crop which was treated with 120 kg K ha-1 from the Sulphate of Potash (SOP) fertilizer. Among the treatments the highest bulb yield (14.33 t ha-1) was obtained with 120 kg K ha-1 and the lowest (6.92t ha-1) from the control. The highest disease incidents (65.67%) were recorded from the control followed by the plots which were treated with 60 kg K ha-1 (62.28%). The lowest disease incidence (49.22%) was recorded from 180 kgha-1 SOP treated plot. Application of 120 kg K ha-1 from K2SO4 along with a blanket dose of N100P50S20B1.5Zn4 kgha-1 and 5 ton cowdung ha-1 appeared to be the optimum dose for maximizing the bulb yield of summer onion. Bangladesh Agron. J. 2017, 20(1): 37-43